The case for microsimulation frameworks for integrated urban models - Eric J. Miller (Journal of Transport and Land Use, 2018)
The primary objective of this paper is to “make the case” for adoption of microsimulation frameworks for development of integrated urban models. Similar to the case of activity-based travel models, microsimulation in integrated urban models enables such models to deal better with: heterogeneity and non-linearity in behavior; identification of the detailed spatial and socioeconomic distribution of impacts, benefits and costs; tracing complex interactions across agents and over time; providing support for modelling memory, learning and adaptation among agents; computational efficiency; and emergent behavior. The paper discusses strengths, weaknesses and challenges in microsimulating urban regions, including the extent to which microsimulation models are still subject to Lee’s famous “seven sins of large-scale modelling,” as well as the extent to which they may help alleviate or reduce these sins in operational models. The paper concludes with a very brief discussion of future prospects for such models.